URGENT DIAGNOSTICS OF CEREBRAL VENOUS TROMBOSIS - L. M. Tibekina; T. A. Shumakova; A. A. Nikolaeva; Yu. A. Shcherbuk (Вестник хирургии имени И.И. Грекова)
Investigations were carried out in 24 patients in order to evaluate information value of the data of clinical, laboratory, neuroradiological methods of research and develop the diagnostic algorithm in case of cerebral venous thrombosis (CVT). The main group consisted of 11 patients (7 male, 4 female, average age 49,1±4,3) with CVT. The comparison group included 13 patients (6 male, 7 female; average age 68,1±9,5) with ischemic stroke (IS) of moderate severity. There were revealed changes in blood and cerebrospinal fluid (CSF) as form of leukocytosis of blood and moderately increased cell count with elevated protein in CSF and blood in case of CTV. The authors noted an elevated protein in CSF and blood and leukocytosis with predominant lymphopenia in blood and neurophilic predominance in CSF within the reference range of CSF in patient with ischemic stroke. The epileptic attacks, meningeal syndromes, headaches were more often among clinical syndromes at CTV than in case of ischemic stroke. The algorithm of neuroimaging research methods and modes of MRI were determined and allowed an effective diagnostics of damages of venous sinuses, superficial and deep cerebral veins in case of urgent hospitalization of patients. It was possible to suggest the venous pathology in 7 (63,6%) cases due to SKT (without contrast) and in case of application of MR venography (2D TOFmode), there were revealed 100% of cases.